Product safety and security in the global supply chain: Issues, challenges and research opportunities - Marucheck, Ann; Greis, Noel; Mena, Carlos; Cai, Linning (Elsevier Science B.V., Amsterdam., 2011)
A number of high profile product safety events and recalls have heightened public attention to the safety and security of the products that people consume and use. While product safety isn’t a new topic, the effect of the global supply chain in creating or exacerbating safety risks and vulnerabilities is both timely and relevant. In this essay we focus on how the field of operations management can provide fresh perspectives and insights in addressing the challenges of product safety and security in the global supply chain. We first examine the product safety issues and challenges that arise in five industries that are increasingly globalizing their supply chains: food, pharmaceuticals, medical devices, consumer products and automobiles. We describe four areas where operations management theory and methodologies can provide fresh insights and innovative solutions in addressing these problems; regulation and standards, product lifecycle management, traceability and recall management, and supplier relationships.